Diversity in the work–life interface: introduction to the special issue. Issue 5 (30th May 2020) - Beauregard, T. Alexandra; Adamson, Maria; Kunter, Aylin; Miles, Lilian; Roper, Ian
Abstract : Purpose: This article serves as an introduction to six articles featured in a special issue on diversity in the work–life interface. This collection of papers contains research that contemplates the work–life interface in different geographic and cultural contexts, that explores the work–life experiences of minority, marginalized and/or underresearched groups of workers and that takes into account diverse arrangements made to fulfill both work and nonwork responsibilities. Design/methodology/approach: This introductory article first summarizes some of the emerging research in this area, introduces the papers in this special issue and links them to these themes and ends with highlighting the importance of using an intersectional lens in future investigations of the work–life interface. Findings: These six articles provide empirically based insights, as well as new theoretical considerations for studying the interface between paid work and personal life roles. Compelling new research directions are identified. Originality/value: Introducing the new articles in this special issue and reviewing recent research in this area brings together the work–life interface scholarship and diversity management studies and points to the necessity for future investigations to take an intersectional and contextualized approach to their subject matter.